The Supplier Evaluation in Bamboo Karya Manunggal Furniture Industry Using Analytic Network Process (ANP) Method - Hanan, Zatil; Nurdin, Riani; Astuti, Marni (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Suppliers are sources providing the first material where the chain of goods distribution will start. Nowadays, the method of making decisions on the supply of bamboo raw materials for UKM Karya Manunggal is by conventional (intuition), so that it is often inappropriate in selecting the suppliers. Along with the increasingly fierce level of competition in the field of bamboo furniture, Karya Manunggal needs to review the strategy in the competition and to evaluate the ability of suppliers who are the main raw material providers. Therefore, the authors conducted a study that can be used by companies to measure the weight of each supplier by applying the Analytic Network Process (ANP) method. The Analytic Network Process (ANP) method was used to determine the ratio of the inner dependence and the outer dependence and the feedback. There were 7 criteria which were divided into 14 sub criteria and 6 alternatives used in this study. The final result was Arista Bambu with a weight of 0.2327, followed by Pak Wagiyo with 0.2106, Pak Paimin with 0.1737, Pak Gianto with 0.1506, Pak Tofa with 0.1217, and Pak Manto with 0.1107 . This study was assisted by using Super Decision Software, Microsoft Excel.